Gender History in Newfoundland Pentecostalism: Alice Belle Garrigus and Beyond - Ambrose, Linda McGuire (PentecoStudies, 2016)
This Canadian case study explores how Pentecostal history intersects with questions of gender, authority and power. Alice Belle Garrigus was the founder of Newfoundland Pentecostalism but some have argued that it was the men she recruited who really expanded the movement. This paper sets aside the depictions of Garrigus as a marginalized aging woman to listen instead to her own voice as she recounted her testimony of call and ministry. A 1929 photograph of Pentecostal workers is used to explore gender and leadership. By incorporating congregational histories, autobiographical writings, and an oral history account, a more complete cast of workers emerges and the gendered story of Pentecostalism's early days in Newfoundland is rendered more complex. Moving beyond a simple binary debate about whether it was Alice or the men who really account for the spread of Pentecostalism, the paper argues instead that the best explanation for how Pentecostalism was established in Newfoundland is that the movement relied upon a complex network of both male and female actors. That complexity sometimes has been obscured because of the gendered ways in which the history of Newfoundland Pentecostal history has been written and recounted, with an emphasis on male leadership and their contributions.